A26 Molecular epidemiology of hepatitis E virus in Ireland 2016. Issue 1 (22nd August 2019) - Bennett, Charlene; Dunford, Linda; Coughlan, Suzie; De Gascun, Cillian; O'Gorman, Joanne
Abstract: Foodborne viruses such as hepatitis E virus (HEV) pose an increasing risk to public health and to confidence in Irish food. Hepatitis E has been acknowledged as a significant pathogen of likely zoonotic transmission, with pork products and shellfish being implicated as potential sources. The European Food Safety Authority has recommended that systematic strain typing of viruses in humans, animals, and food commodities is needed to improve understanding of etiological agents and foodborne transmission pathways, in particular for HEV. The dominant autochthonous genotype of HEV in Europe is genotype 3, thought to be associated with consumption of contaminated food, specifically pork products. However, little is known about the epidemiology of HEV in Ireland. In 2016, HEV became a notifiable disease in Ireland. Following this, as part of the Department of Agriculture, Food and the Marine-funded FoVIRA study, the molecular epidemiology of HEV in Irish clinical samples has been characterized for the first time. HEV RNA-positive clinical specimens from 2016 were genetically characterized ( n = 14). A 450 nucleotide fragment of the ORF2 region of the HEV genome was amplified, with contiguous sequence assembly performed using DNA Lasergene v14. Sequences were aligned with ClustalW implemented in Bioedit v7.1.9 and compared to reference strains from GenBank. A maximum likelihood phylogenetic tree was constructed using the Hasegawa–Kishino–Yano model and a discrete gamma distribution to model evolutionary rate distances between sites. Evolutionary analyses were conducted in MEGA7. Statistical support was provided by bootstrapping with 1, 000 replicates. Fourteen strains belonged to genotype 3 and were classified as the following subtypes: 3c ( n = 7), 3e ( n = 4), 3f ( n = 1), 3 untyped ( n = 1), and 1 untyped. Phylogenetic analysis showed the formation of two distinct clusters of genotype 3:3abchij and 3efg, with strong bootstrap support. A genotype 1 was detected and found to be associated with travel. Data generated from this research will contribute to a risk exposure assessment and will be used to identify potential control points and risk mitigation measures for viral foodborne pathogens. This study will provide a unique opportunity to build national capability in the area of food testing within Irish public laboratories.